Comparison of Intramedullary Interlocking Nailing (IMLNG) and Minimally Invasive Plate Osteosynthesis (MIPO) in Treating Extra Articular Distal Tibial Fractures - Muhammad Zeb Khan, Mohammad Khalid, Malik Mohammad Yasin Awan, Muhammad Safdar, Adeel Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Due to limited blood flow and sparse soft tissue coverage, treating distal tibia fractures presents a considerable challenge for orthopaedic surgeons. Objective: Our study’s objectives were to compare the outcomes of the two treatment modalities of minimally invasive plate osteosynthesis (MIPO) and intramedullary nailing (IMN) for extraarticular distal tibia fractures. Study Design: Randomized Controlled Trial Place and Duration of the Study: This study was conducted at Department of Orthopedic and Spine Surgery Sughra Shafi Medical Complex, Narowal from March 2021 to March 2022. Material Methods: During A total of 59 patients ( 30 in IMLN group and 29 in MIPO group), both male and female, with AO Type A, b and C distal tibial fractures lasting less than three days and ages ranging from 20 to 60, were enrolled for this research. At the most recent follow-up, clinical and radiological data were assessed. Results: The average duration to union was 21.9 weeks in the IMN group and 19.9 weeks in the MIPO group, and all of the examined patients eventually recovered. In the IMN group, the time to union was substantially greater (p= 0.001). Conclusion: Low operating, union, and hospitalisation times make MIPO advantageous. In order to lessen the morbidity of these patients, we advise using the minimally invasive plate osteosynthesis (MIPO) procedure as the first line of treatment for distal tibia fractures.. Keywords: Distal tibia fracture, minimally invasive plate osteosynthesis, intramedullary nailing,